ASHOBAH BILGHOIR; PRAKTIK DAN METODE PENYELESAIANNYA BERDASARKAN SYAJARAH AL-MIRATS - Raja Ritonga (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2023)
Islamic inheritance is synonymous with the comparison of the share between male and female heirs. Furu' and hawasyi heirs often become polemics over the value of the portion received by female heirs in particular. In practice, the share of inheritance for men and women is influenced by the existence of one another. Therefore the value of the part they will receive is determined by the whereabouts of each. This research will describe the practices and methods of solving the inheritance of ashobah bilghoir heirs based on the concept of syajarah al-mirats. The method used is a qualitative form with a type of library research. In this study, researchers collected data by searching some books, books, articles, and other scientific works related to the research theme. Furthermore, the data findings were analyzed descriptively with a conceptual approach. The results of this study explain that the practice of ashobah bilghoir inheritance can occur in the inheritance group of children, grandchildren, great-grandchildren, siblings, and half-brothers of the father. Meanwhile, in the settlement method, each male heir is counted as two people and one woman heir is still counted as one person. In addition, great-grandsons can have their ashobah combined with granddaughters.